Outcomes of Pulp Therapy in Traumatized Primary and Permanent Teeth in Children (Dhaka Shishu (Children) Hospital Journal, 2026)
Background: Traumatic dental injuries (TDIs) in pediatric patients can significantly impact both primary and permanent dentitions, requiring timely and appropriate pulp therapy to ensure optimal outcomes. Objective: This study aimed to evaluate the types of dental trauma, pulp therapy modalities, and clinical and radiographic outcomes in children following traumatic injuries. Methods: This cross-sectional observational study was conducted in the Department of Dentistry at Bangladesh Shishu Hospital & Institute, Dhaka, from January to December 2023. A total of 50 pediatric patients (aged 3–12 years) with TDIs involving primary (n=30) or permanent teeth (n=20) were included using purposive sampling. Children with systemic conditions, developmental anomalies, or incomplete records were excluded. Clinical and radiographic evaluations were performed at baseline and after 6 months to assess treatment outcomes. Results: Most patients were aged 7-9 years (42%), and 58% were male. Primary teeth were more frequently affected. Complicated crown fractures (44%) were the most common type of trauma, followed by uncomplicated crown fractures (22%) and luxation injuries (20%). Pulpectomy/root canal treatment was the most common pulp therapy (42%), followed by pulpotomy (34%), direct pulp capping (14%), and indirect pulp capping (10%). Apexogenesis and regenerative therapy were applied in select permanent teeth. At 6-month follow-up, 86% of teeth were clinically asymptomatic. Radiographically, 80% showed normal healing. Minor complications included pain, swelling, sinus tract, and mobility. Conclusion: Pulp therapies in traumatized primary and permanent teeth yielded favorable clinical and radiographic outcomes over a 6-month period. Early diagnosis and appropriate treatment selection are key to preserving dental health in pediatric trauma cases.DS (Child) H J 2024; 40(1): 35-40